2021
DOI: 10.1021/acs.organomet.1c00572
|View full text |Cite
|
Sign up to set email alerts
|

16-Electron Half-Sandwich Rhodium(III), Iridium(III), and Ruthenium(II) Complexes as Lysosome-Targeted Anticancer Agents

Abstract: The 18-electron half-sandwich platinum group (Rh, Ru, Ir, and Os) metal anticancer complexes have been largely reported due to their easy tunable structure, high potency toward cancer cells, and specific mechanism of actions. However, the 16electron (without the leaving group Cl − ) half-sandwich complexes and their biological evaluation are rarely investigated. With an easy access to the required α-keto-β-diimine ligands using m-CPBA as oxidant, we herein reported the synthesis and characterization of a panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The chloro-bridged bimetallic Ir­(III), Rh­(III), and Ru­(II) precursors D1 – D8 were synthesized using the reported procedures. Reactions of these precursors with the ligands L1 – L3 and NH 4 PF 6 in a mixture of dichloromethane and methanol for 5 h at an ambient temperature gave rise to the complexes Ir1 – Ir7 , Rh1 – Rh5 , and Ru1 – Ru4 in 41–59% isolated yields (Scheme ). All of these complexes were soluble in common solvents such as DMSO, dichloromethane, methanol, and acetonitrile and showed sufficient stability in air.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The chloro-bridged bimetallic Ir­(III), Rh­(III), and Ru­(II) precursors D1 – D8 were synthesized using the reported procedures. Reactions of these precursors with the ligands L1 – L3 and NH 4 PF 6 in a mixture of dichloromethane and methanol for 5 h at an ambient temperature gave rise to the complexes Ir1 – Ir7 , Rh1 – Rh5 , and Ru1 – Ru4 in 41–59% isolated yields (Scheme ). All of these complexes were soluble in common solvents such as DMSO, dichloromethane, methanol, and acetonitrile and showed sufficient stability in air.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute emission quantum yields of selected complexes Ir1 , Rh1 , and Ru1 are relatively low ( Ir1 : 0.39%, Rh1 : 0.31%, Ru1 : 0.15%) in methanol solutions. This weakly photoluminescent behavior was also observed in the previously reported half-sandwich Ir­(III), Rh­(III), and Ru­(II) complexes. ,, However, the photoluminescent characteristic of these complexes rendered it possible to explore MoAs by bioimaging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bimetallic iridium­(III), rhodium­(III), and ruthenium­(II) precursors [(η 5 -C 5 Me 5 )­MCl 2 ] 2 (M = Ir ( D1 ); Rh ( D5 )), [(η 5 -Cp R )­MCl 2 ] 2 (Cp R = C 5 (CH 3 ) 4 R, R = Cy (M = Ir ( D2 ); M = Rh ( D6 )), 2-methylbenzene (M = Ir ( D4 )), 3,5-bis­(trifluoromethyl)­benzene) (M = Ir ( D3 ); Rh ( D7 )) and [(η 6 -arene)­RuCl 2 ] 2 ( D8 – D10 ) were prepared by the reported methods ,, or using the modified procedure ( D6 ; see the Supporting Information). It should be noted that the arene ligand of ruthenium complexes is different from that of iridium and rhodium complexes since the presence of η 6 -arene substituent was identified to stabilize ruthenium complexes in the +2 oxidation state by being relatively inert to displacement. Moreover, another motivation for the development of air-stable η 6 -arene ruthenium­(II) complexes was the activation by reduction hypothesis, which suggested that active ruthenium­(II) species may be formed in vivo from ruthenium­(III) complexes. Scheme shows the synthetic procedure of zwitterionic phosphine–imine half-sandwich iridium­(III), rhodium­(III), and ruthenium­(II) complexes containing sulfonate moiety.…”
Section: Resultsmentioning
confidence: 99%